Iris - Bayley, John 1925-2015 (Duckworth, 2002)
In this memoir, Bayley describes the life he shared with his wife, Iris Murdoch, afflicted with Alzheimer's disease. He explains how he coped emotionally and practically with the illness that beset the woman he loved and cherished.
Enth.: Iris, a memoir of Iris Murdoch. -Iris and her friends, a year of memories
Keywords: Murdoch, Iris <1919-> - Biography; Murdoch, Iris -- Biography; Murdoch, Iris -- 1919-1999; Bayley, John -- 1925-2015; Geschichte 1900-2000; Alzheimer's disease -- Patients -- Biography; Novelists, English -- 20th century -- Biography; Women novelists, English -- 20th century -- Biography; Autobiografie